2014
DOI: 10.4103/2229-5178.137780
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function tests in cases of polymorphic light eruption: A case-control study

Abstract: Background:Polymorphic light eruption (PLE) has been found to be associated with thyroid function abnormalities.Aim:To study clinicoepidemiological features of PLE and to study and compare thyroid function tests (TFTs) in cases of PLE.Materials and Methods:The study included 100 cases of PLE and age- and sex-matched controls attending a skin outpatient department. The clinical and epidemiological features were recorded. Both cases and controls were tested for thyroid-stimulating hormone (TSH). In case of abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…It was found statistically significant. This findings correlate well with the study conducted by Sharma et al 7 ., in 2014 in which TSH was high in 24%, low in 1% of cases and high in 6%, low in 1% of controls Chi square-31, df-17, P value -0.01 (S) In our study, low T3 and T4 level were found only in 11.42% of cases. While T3 and T4 level were normal in 5.71% cases and 2.85% controls which was not statistically significant ( Table 2).…”
Section: Resultssupporting
confidence: 94%
“…It was found statistically significant. This findings correlate well with the study conducted by Sharma et al 7 ., in 2014 in which TSH was high in 24%, low in 1% of cases and high in 6%, low in 1% of controls Chi square-31, df-17, P value -0.01 (S) In our study, low T3 and T4 level were found only in 11.42% of cases. While T3 and T4 level were normal in 5.71% cases and 2.85% controls which was not statistically significant ( Table 2).…”
Section: Resultssupporting
confidence: 94%
“…Thyroid dysfunction is not rare in PLE. Indeed, hypothyroidism is detected significantly more often in patients with PLE than in controls 7,37 . It has been recently shown that in state of hypothyroidism, the skin has an increased lipid peroxidation due to a decreased antioxidant defense 38 .…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…In a study by Seetharam et al, [ 4 ] nearly 25.9% cases were hypothyroid along with polymorphic light eruption, and only 7.5% of controls were hypothyroid. Sharma et al, [ 3 ] in 2014 found out that nearly 18% cases and 5% of controls were found to have overt hypothyroidism along with subclinical hypothyroidism in 6% cases and 1% controls. Hasan et al, [ 5 ] found out that polymorphic light eruption had an autoimmune basis for origin and females showed a higher number of cases compared to males.…”
Section: Discussionmentioning
confidence: 99%
“…In dermatoses such as melasma and polymorphic light eruption which are sunlight-associated, thyroid function disorders have been noted [3][4][5]. Herein we describe a comparative study of biochemical evaluation of thyroid function test carried out among 60 cases of PMLE with an equal number of controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation